Edukasi Etika Kristen dalam Bermedia Sosial bagi Generasi Muda di GWI Jemaat Wesleyan Metodist Tanjung Selamat - Thomson Siallagan (ARDHI : Jurnal Pengabdian Dalam Negri, 2026)
The era of digital disruption has brought significant moral and spiritual challenges for young people in their use of social media. This study aims to analyze the implementation of Christian ethics education in social media use among youth at the GWI Wesleyan Methodist Congregation of Tanjung Selamat as an effort to develop digital character grounded in Christian values. The study employed a community service approach using participatory methods through pre-tests, post-tests, Focus Group Discussions (FGD), reflective discussions, and digital literacy practices. The theological foundation of this study is based on Wesleyan social ethics, which emphasizes the integration of personal holiness and social holiness in digital life. The educational program also integrated the four pillars of digital literacy, digital skills, digital culture, digital ethics, and digital safety, into a contextual Christian Religious Education framework. The findings indicate a significant improvement in digital literacy understanding, ethical awareness, critical thinking toward digital information, and behavioral transformation in the responsible and value-based use of social media according to Christian principles. This transformation was reflected in increased awareness of digital footprints, stronger personal account security, the removal of negative content, and participants’ initiatives to create spiritual and educational content on social media. The study concludes that Christian ethics education based on digital literacy can serve as an effective means of moral and social transformation for young people while highlighting the strategic role of the church in shaping a humane, peaceful, and Kingdom of God-oriented digital character in the digital era.